Investigating the emergence and spread of tuberculosis in South Africa - Campbell, Tessa (Department of Archaeology, 2019)
Tuberculosis is the leading cause of death in South Africa and, while the disease is clearly very relevant today, little has been done to understand its emergence locally from a deep history perspective. Bioarchaeological investigations of tuberculosis have received much attention in Europe and North America but, with the exception of Egypt, the African continent has not been well-evaluated in this regard despite numerous genetic studies suggesting an African origin for the disease. This thesis aims to identify cases of skeletal tuberculosis in the archaeological record of South Africa and, aided by historical literature, trace its geographical and temporal origins in order to inform a broader local and global understanding of this ancient pathogen. Ancient DNA detection and analysis was also attempted in order to compliment skeletal diagnoses and obtain strain informative sequences. Preservation, demographic and paleopathological data were collected for 2321 individuals, representing the majority of South African Holocene and historical remains curated in local institutions, and a thorough description of this extensive dataset is presented. Only twelve individuals showing pathology suggestive of tuberculosis were identified. All potentially date to the colonial period; however, two individuals likely predate direct European contact. The association of these individuals with Iron Age populations may suggest a link between an early introduction of the disease and East African trade but caution in this interpretation is advised due to the tentative diagnoses in both cases. The skeletal record supports the major events identified in the literature; an early focus of disease along the Orange River and at the major port city of Cape Town, followed by a cluster of cases in Kimberley associated with mining activities and, finally, a spread to rural agricultural communities. Of the nine individuals subject to ancient DNA analysis using silicabased extraction protocols and quantitative PCR, Mycobacterium tuberculosis complex (MTBC) DNA was identified in only three. Attempts to obtain MTBC strain informative sequences through next generation sequencing were unsuccessful. This is the first study in South Africa to report the detection of ancient pathogen DNA; however, despite a possible African origin for tuberculosis, there is no evidence to support a pre-colonial presence of the disease in South Africa.